Outbreak of carbapenemase-producing Enterobacteriaceae associated with a contaminated water dispenser and sink drains in the cardiology units of a Korean hospital. Issue 4 (April 2020) - Jung, J.; Choi, H-S.; Lee, J-Y.; Ryu, S.H.; Kim, S-K.; Hong, M.J.; Kwak, S.H.; Kim, H.J.; Lee, M-S.; Sung, H.; Kim, M-N.; Kim, S-H.
Summary: Background: Concerns are growing over the importance of the hospital water environment for the transmission of carbapenemase-producing Enterobacteriaceae (CPE). Aim: To report a large outbreak in the cardiology units involving intensive care units (ICUs) and wards at a tertiary-care hospital. Methods: This was a contact tracing, case–control study to find the risk factors for acquisition of CPE and environmental sampling was performed during a CPE outbreak between July and December 2018. Findings: A total of 87 patients with CPE infection or colonization were identified in the cardiology units of the Asan Medical Centre. Diverse organisms were identified containing bla kp c, bla NDM-1, bla VIM or bla IMP, bla OXA-48, and co-producing organisms. A case–control study indicated that using the sinks in the ward patient room bathroom for teeth brushing was associated with CPE acquisition (83% vs 30%; P =0.03). The environment was cultured and Klebsiella pneumoniae carbapenemase (KPC)-producing Escherichia coli was isolated from a water dispenser and New Delhi metallo-beta-lactamase (NDM) 1-producing Citrobacter freundii and Enterobacter cloacae from sinks in patient rooms. Pulsed-field gel electrophoresis (PFGE) analysis of KPC-producing E. coli from patients and the water dispenser in ICU and NDM-1-producing E. cloacae from the patient and sink drain showed the same pulsotypes. Conclusions: The water dispenser and sink drain were suspected as possible reservoirs of CPE in this outbreak. Close contacts with contaminated water such as tooth brushing were identified as risk factors for CPE acquisition. Education for the adequate use of the water environment system as well as the control of the hospital water environment should be implemented to prevent the CPE outbreaks.